Transgenerational Effects and Epigenetic Memory in the Clonal Plant Trifolium repens - Rendina González, Alejandra Pilar; Preite, Veronica; Verhoeven, Koen J. F.; Latzel, Vít (Frontiers in Plant Science, 2018)
Transgenerational effects can modify phenotypes of offspring generations playing thus a potentially important role in ecology and evolution of many plant species. These effects have been studied mostly across generations of sexually reproducing species. A substantial proportion of plant species are however reproducing asexually, for instance via clonal growth. Transgenerational effects are thought to be enabled by heritable epigenetic modification of DNA, although unambiguous evidence is still scarce. On the clonal herb white clover (Trifolium repens), we tested the generality of clonal transgenerational effects across five genotypes and five parental environments including soil contamination and above-ground competition. Moreover, by genome wide-methylation variation analysis we explored the role of drought, one of the parental environments that triggered the strongest transgenerational effects. We tested the induction of epigenetic changes in offspring generations using several intensities and durations of drought stress. We found that transgenerational effects of different environments were highly genotype specific and all tested environments triggered transgenerational effects at least in some genotypes. In addition, parental drought stresses triggered epigenetic change in T. repens and most of the induced epigenetic change was maintained across several clonal offspring generations. We conclude that transgenerational effects are common and genotype specific in clonal plant T. repens and potentially under epigenetic control.